2014
DOI: 10.1097/brs.0000000000000086
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Spinal Cord Compression by Cervical Ossification of the Posterior Longitudinal Ligament Evaluated by Kinematic Computed Tomography Myelography

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 27 publications
1
25
0
2
Order By: Relevance
“…Second, CTM provides clear contrasted images with thinner slices and higher image resolution in axial and sagittal reconstructed slices, which effectively demonstrate dynamic changes in spinal cord compression. 6,7 Histopathological analysis of the epidural scar revealed chronic inflammation caused by acellular, amorphous and basophilic deposits. These materials appeared exogenous and were presumably remaining surgical materials from the first operation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, CTM provides clear contrasted images with thinner slices and higher image resolution in axial and sagittal reconstructed slices, which effectively demonstrate dynamic changes in spinal cord compression. 6,7 Histopathological analysis of the epidural scar revealed chronic inflammation caused by acellular, amorphous and basophilic deposits. These materials appeared exogenous and were presumably remaining surgical materials from the first operation.…”
Section: Discussionmentioning
confidence: 99%
“…3,[8][9][10] Miura et al 11 suggested that it is necessary to evaluate spinal cord compression in patients with cervical myelopathy at different neck positions both pre-operatively and post-operatively because cord compression appeared to vary by position. Although the spinal cord was likely to be compressed during extension, 7,12 greater spinal cord compression was observed during neck flexion with a higher occupying ratio of the OPLL. 12 Clinically, the influences of dynamic factors on the cervical myelopathy have been radiographically examined by evaluating changes in the cross-sectional area (CSA) of the spinal cord or the occupying ratio of spinal cord by the OPLL during flexion-extension positions.…”
Section: Introductionmentioning
confidence: 97%
“…Although the spinal cord was likely to be compressed during extension, 7,12 greater spinal cord compression was observed during neck flexion with a higher occupying ratio of the OPLL. 12 Clinically, the influences of dynamic factors on the cervical myelopathy have been radiographically examined by evaluating changes in the cross-sectional area (CSA) of the spinal cord or the occupying ratio of spinal cord by the OPLL during flexion-extension positions. Recently, the kinematic CT myelography and dynamic multidetector-row CT are used to investigate flexion and extension motion on the spinal cord in patients with the cervical OPLL.…”
Section: Introductionmentioning
confidence: 97%
“…Computed tomography following myelography (CTM) plays an important role in the accurate diagnosis of various lesions in the spinal canal lesions that cannot be diagnosed by magnetic resonance imaging (MRI) [1,2]. In our clinic, almost all admitted patients suffering from spinal lesions are examined by CTM, during which we have noted unusual flow patterns of contrast dye into the anterior median fissure (AMF).…”
Section: Introductionmentioning
confidence: 99%